Nostalgia contretemps: A theory of contemporary South African literature - Moonsamy, Nedine (My University, 2014)
Employing Derrida’s contretemps as central to my study, I undertake a close reading of time and nostalgia in contemporary South African fiction as that which is ‘out of joint’ with itself. The main premise of my research involves an illustration of how nostalgic affect is projected towards the ‘lost’ potential of the post-apartheid future, as opposed to the past. I explore how authors represent nostalgia contretemps as a central feature of the cultural imaginary and yet, at the same time, gesture towards its increasing untenably in a ‘post-transitional’ context.